2002
DOI: 10.1128/mcb.22.10.3437-3449.2002
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Large-Scale Chromatin Structure by Estrogen Receptor

Abstract: The estrogen receptor (ER), a member of the nuclear hormone receptor superfamily important in human physiology and disease, recruits coactivators which modify local chromatin structure. Here we describe effects of ER on large-scale chromatin structure as visualized in live cells. We targeted ER to gene-amplified chromosome arms containing large numbers of lac operator sites either directly, through a lac repressor-ER fusion protein (lac rep-ER), or indirectly, by fusing lac repressor with the ER interaction do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
1
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 57 publications
6
80
1
2
Order By: Relevance
“…More recently, footprinting and ChIP studies have revealed the association (Kim et al 2000, Shang et al 2000 and cyclic recruitment (Reid et al 2003) of ERα to estrogen-responsive promoters in the absence of ligand. These findings parallel those of Belmont's group who, reconstructing and visualizing transcriptional regulation and chromatin structure, has found that the apo-ERα was able to decondense chromatin (Nye et al 2002). In this experimental system, decondensation of large-scale chromatin was independent of helix 12 and did not require transcriptional activation by ERα, ligand-induced coactivator binding, or histone hyperacetylation.…”
Section: Role In Repressing Apo-erαsupporting
confidence: 88%
“…More recently, footprinting and ChIP studies have revealed the association (Kim et al 2000, Shang et al 2000 and cyclic recruitment (Reid et al 2003) of ERα to estrogen-responsive promoters in the absence of ligand. These findings parallel those of Belmont's group who, reconstructing and visualizing transcriptional regulation and chromatin structure, has found that the apo-ERα was able to decondense chromatin (Nye et al 2002). In this experimental system, decondensation of large-scale chromatin was independent of helix 12 and did not require transcriptional activation by ERα, ligand-induced coactivator binding, or histone hyperacetylation.…”
Section: Role In Repressing Apo-erαsupporting
confidence: 88%
“…NYE5 (a GFP-lac rep expression plasmid) was made in a manner similar to NYE4 (8) except that an AscI site was added at the end of GFP-lac rep by silent mutations A3167G and A3170C just downstream of a PvuII site. NYE4 and NYE5 are functionally equivalent in coding for the dimer, tight binding form of the lac repressor.…”
Section: Subcloningmentioning
confidence: 99%
“…We previously used this system to investigate the effects of ER on large-scale chromatin structure (8). In that work, we investigated the structure of the fibers produced by targeting various mutations and truncations of the ER to the A03_1 lac operator array.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout most of the cell cycle, this amplified chromosome region is condensed into a compact mass. Targeting certain transcriptional activators to this heterochromatic locus via a lac repressor fusion protein leads to large-scale decondensation of this region (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%